Genome-Wide Analysis Identifies Two Susceptibility Loci for Positive Thyroid Peroxidase and Thyroglobulin Antibodies - Matana, Antonela; Boutin, Thibaud; Torlak, Vesela; Brdar, Dubravka; Gunjača, Ivana; Kolčić, Ivana; Boraska Perica, Vesna; Punda, Ante; Polašek, Ozren; Barbalić, Maja; Hayward, Caroline; Zemunik, Tatijana (The journal of clinical endocrinology and metabolism, 2020)
Abstract Introduction Thyroid peroxidase (TPO) and thyroglobulin (Tg) are main components of the thyroid gland and play an essential role in thyroid hormone synthesis. The development of antibodies to thyroid peroxidase (TPOAb) and thyroglobulin (TgAb) is the major diagnostic hallmark and early indicator of autoimmune thyroid disease. TPOAb and TgAb are under strong genetic influence; however, genetic factors that determine thyroid antibody positivity are largely unknown. Materials and Methods To identify novel loci associated with TPOAb and/or TgAb positivity, we performed a genome-wide meta-analysis in a total of 2613 individuals from Croatia. Participants with elevated plasma TPOAb and/or TgAb were defined as cases (N = 619) and those with TPOAb and TgAb within reference values were defined as controls (N = 1994). Results We identified 2 novel loci, of which 1 is located within the YES1 gene (rs77284350, P = 1.50 × 10–8), and the other resides within the IRF8 gene (rs16939945, P = 5.04 × 10–8). Conclusions Although the observed variants were associated with TPOAb and TgAb positivity for the first time, both YES1 and IRF8 were previously linked to susceptibility to other autoimmune diseases, and represent plausible biological candidates. This study adds to the knowledge of genetics underlying thyroid antibodies and provides a good basis for further research.